Isolation, screening and in-vitro characterization of plant growth-promoting Bradyrhizobium isolates from the nodules of Bambara groundnut (Vigna subterranean) for potential use as bioinoculants - Seidu, Osman Abdulai; Githiri, Stephen Mwangi; Wesonga, John Mwibanda; Ngumi, Victoria Wambui (Frontiers in Sustainable Food Systems, 2025)
Bambara groundnut (Vigna subterranean) is a resilient leguminous crop that can withstand drought conditions and is commonly grown in arid regions where soils are degraded and of low fertility status. Although the crop can fix nitrogen, its yields frequently fall short of their maximum potential which can be attributed to association with ineffective rhizobia strains. In the present study, we isolated, screened, and in-vitro characterized Bradyrhizobium isolates from the root nodules of Bambara groundnuts with plant growth promoting properties for potential use as bioinoculant. Root nodules were sampled from JKUAT farm where healthy Bambara groundnut plants were growing. Ten isolates with slow growth rate were isolated. The 10 isolates were screened using morphological, biochemical and molecular (16S rRNA gene sequencing) techniques. The sequence analysis established that all isolates were congeneric with Bradyrhizobium. In addition, all the isolates showed Nitrogen-fixing potentials and also had significant (p < 0.005) ability to solubilize phosphate in the range of 0.77 ± 0.771–3.22 ± 0.368 phosphate solubilizing index. Further, isolates P4A17, P4A18, P4A16, P4A6 and C2 produced IAA concentrations of 54.97 ± 3.21–108 ± 12.10 μg/mL. However, none of the isolates could produce HCN. The isolates were assessed further on their ability to grow in varied physiological conditions. Among them, P4A6 and P4A18 demonstrated higher growth potential under pH 3, pH 5, pH 9, pH 11, 1% NaCl, 3% NaCl, 5% NaCl and high temperature range of 40°C–50°C than the rest of the isolates. Given the in-vitro results, these isolates are promising bioinoculant (biofertilizer) candidates and, ought to be further tested in greenhouse and field conditions for Bambara groundnut production.